2015
DOI: 10.1001/jamaoto.2014.3550
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Epithelial Cell Response toStaphylococcus aureusBurden in Chronic Rhinosinusitis

Abstract: Importance Chronic rhinosinusitis (CRS) is an inflammatory disorder of the nose and paranasal sinuses. Staphylococcus aureus is increasingly linked with CRS exacerbations. Little is known about how bacteria activate inflammatory pathways that contribute to CRS. Objective Here, we developed an in-vitro co-culture system to explore how infection with Staphylococcus aureus stimulates innate immune responses of sinonasal epithelial cells (SNEC). Design, Setting, and Subjects SNEC were collected from 13 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Previous work demonstrated an increase in expression of these mediators as a result of infection of cultured SNECs with S. aureus 25 . To explore if antibiotic-mediated ROS formation promotes a pro-inflammatory state, we looked at the expression of TNF -α and IL-8 in SNECs following 24-hours of treatment with no antibiotics, clarithromycin, levofloxacin or amoxicillin (Figure 3A).…”
Section: Resultsmentioning
confidence: 88%
“…Previous work demonstrated an increase in expression of these mediators as a result of infection of cultured SNECs with S. aureus 25 . To explore if antibiotic-mediated ROS formation promotes a pro-inflammatory state, we looked at the expression of TNF -α and IL-8 in SNECs following 24-hours of treatment with no antibiotics, clarithromycin, levofloxacin or amoxicillin (Figure 3A).…”
Section: Resultsmentioning
confidence: 88%
“…), urinary infections [54,55], and respiratory infections (e.g. rhinosinusitis [56,57], and food poisoning [58][59][60]. It may be also involved in systemic infections [61,62].…”
Section: Staphylococcus Aureus Germs Are Often Involved In Local Imentioning
confidence: 99%
“…This mucosal surface is part of the first line innate defense as this is the site where pathogens interface with hosts. Previous in vitro studies have shown that epithelial cells infected with wild type S. aureus had increased expression of cytokines/chemokines including interleukin (IL)6 (Damm et al, 2006; Sachse et al, 2010), CXCL8 (Damm et al, 2006; Kohanski and Lane, 2015) and tumor necrosis factor (TNF) (Li et al, 2009; Kohanski and Lane, 2015) and tissue remodeling factors such as matrix metalloproteinases (MMPs) (Homma et al, 2015). An in vitro study by Tuchscherr et al showed increased expression of C-C motif chemokine ligand (CCL) 5, C-X-C motif ligand (CXCL) 10 and 11, and intracellular adhesion molecule (ICAM)1 when endothelial cells were infected with wild type S. aureus but not S. aureus SCVs (Tuchscherr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%